Social deprivation in patients requiring pelvic exenterative surgery. (4th July 2016) - Radwan, R. W.; Coyne, P. E.; Jones, H. G.; Evans, M. D.; Davies, M.; Harris, D. A.; Beynon, J.
Abstract: Aim: Pelvic exenteration is an aggressive operation for locally advanced rectal cancer. Social deprivation has been shown to reduce life expectancy and has been linked to a poorer outcome in patients with colorectal cancer. The aim of this study was to analyse the effect of social deprivation scores on the outcome in these complex patients. Method: A retrospective review of all patients undergoing pelvic exenteration for primary rectal cancer between 2006 and 2014 was performed. Deprivation scores were calculated for all patients using the Welsh Index of Multiple Deprivation. Patients were then grouped into quartiles, from Q1 (most deprived) to Q4 (least deprived). The primary outcome measure was 5‐year survival. Results: In all, 120 patients were included (65 female) with a median age of 64 (31–90) years. No differences between quartiles were identified for neoadjuvant therapy ( P = 0.687) or type of exenteration ( P = 0.690). The median length of stay was significantly higher in the most deprived groups (Q1–Q2; P = 0.023). There was a significant difference in survival between the groups, with lowest 5‐year survival rates (53%) in the most deprived quartile (Q1) ( P = 0.015). Conclusion: Social deprivation is significantly associated with postoperative length of stay and survival in patients undergoing pelvic exenteration for primary rectal cancer.